2022
DOI: 10.1111/jopr.13485
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of the Effect of 3D Printing Orientation on the Accuracy of Implant Surgical Templates Fabricated By Desktop Printer

Abstract: Purpose To evaluate the effect of different 3D printing orientations on internal and seating accuracy of implant surgical templates fabricated by a digital light processing (DLP) printer. Materials and methods A single maxillary model with a missing central incisor was used to design a surgical template for single implant placement. According to the printing orientation, three surgical template groups were included in the study: horizontal (H), angled (A) and vertical (V) (n = 10). For the H group, the templat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Hussein et al 27 concluded that build orientation had an influence on the accuracy of the 3D printed partial denture frameworks, especially at a 135-degree angle of maxillary design and 150-degree of mandibular design. Tahir et al 28 had a similar conclusion, that the horizontally printed surgical guides exhibited superior accuracy in comparison with those printed at 45° and 90° orientations. Ko et al 29 showed that build angle and layer height have statistically significant interactive effects on the accuracy of 3Dprinted dental models.…”
Section: Discussionmentioning
confidence: 80%
“…Hussein et al 27 concluded that build orientation had an influence on the accuracy of the 3D printed partial denture frameworks, especially at a 135-degree angle of maxillary design and 150-degree of mandibular design. Tahir et al 28 had a similar conclusion, that the horizontally printed surgical guides exhibited superior accuracy in comparison with those printed at 45° and 90° orientations. Ko et al 29 showed that build angle and layer height have statistically significant interactive effects on the accuracy of 3Dprinted dental models.…”
Section: Discussionmentioning
confidence: 80%
“…Tahir et al evaluated the effect of different printing directions on the placement accuracy of implant surgical templates made by DLP. The results showed that the horizontally printed templates showed excellent accuracy (Tahir and Abduo, 2022).…”
Section: Research Status On Additive Manufacturing Applications In Im...mentioning
confidence: 95%
“…This study utilised a DLP printer, an Asiga MAX UV (385 nm ultraviolet laser; Asiga, Alexandria, New South Wales, Australia), and a desktop 3D consumer-level printer [1,22]. The reference STL images of the implant surgical guides were imported into the Asiga MAX UV slicing software (Asiga Composer, Asiga, Alexandria, New South Wales, Australia).…”
Section: Manufacturing Of 3d-printed Implant Surgical Guidesmentioning
confidence: 99%